Integrated greenhouse systems for mild climates climate conditions, design, construction, maintenance, climate control - von Zabeltitz, Christian (Springer, 2011)
Crop production in greenhouses is a growing industry, especially in mild climates, and is very important for the population as a source of income and clean, fresh food. Greenhouses create optimal climate conditions for crop growth and protect crops from outside pests. At the same time greenhouse production increases water use efficiency and makes integrated production and protection (IPP) possible. This book provides technical instructions for practice (what to do and what not to do) and gives answers to the question: How to produce more clean crops and better quality with less water, less land and less pesticide. Suitable greenhouse constructions and their design, adapted to local climates in subtropical, tropical and arid regions and infrastructure conditions are presented. The necessary climate control measures - light transmittance, ventilation, cooling, heating, and CO2 enrichment - and physical measures for pest control, as well as methods for using solar energy to desalinate salty water are described. The results of theoretical research are transferred into methods for practical use, so that readers are equipped to solve their problems in practice as well as to get stimulation for further research and development.